Diabetes and Frail Older Patients: Glycemic Control and Prescription Profile in Real Life - Anne-Sophie Mangé; Arnaud Pagès; Sandrine Sourdet; Philippe Cestac; Cécile McCambridge (MDPI AG, 2021)
(1) Background: The latest recommendations for diabetes management adapt the objectives of glycemic control to the frailty profile in older patients. The purpose of this study was to evaluate the proportion of older patients with diabetes whose treatment deviates from the recommendations. (2) Methods: This cross-sectional observational study was conducted in older adults with known diabetes who underwent an outpatient frailty assessment in 2016. Glycated hemoglobin (HbA1c) target is between 6% and 7% for nonfrail patients and between 7% and 8% for frail patients. Frailty was evaluated using the Fried criteria. Prescriptions of glucose-lowering drugs were analyzed based on explicit and implicit criteria. (3) Results: Of 110 people with diabetes with an average age of 81.7 years, 67.3% were frail. They had a mean HbA1c of 7.11%. Of these patients, 60.9% had at least one drug therapy problem in their diabetes management and 40.9% were potentially overtreated. The HbA1c distribution in relation to the targets varied depending on frailty status (p < 0.002), with overly strict control in frail patients (p < 0.001). (4) Conclusions: Glycemic control does not seem to be routinely adjusted to the health of frail patients. Several factors can lead to overtreatment of these patients.